Diphacinone with cholecalciferol for controlling possums and ship rats. Issue 2 (2nd April 2020) - Eason, Charles; Shapiro, Lee; Eason, Candida; MacMorran, Duncan; Ross, James
ABSTRACT: Potent second-generation anticoagulant rodenticides such as brodifacoum have been used as more effective alternatives to first-generation anticoagulants, such as warfarin. A combination of diphacinone at 0.005% and cholecalciferol at 0.06% produces a slow-acting bait that is effective at killing possums ( Trichosurus vulpecula ) and rodents. Cage trials with groups of possums and ship rats ( Rattus rattus ) achieved a mortality of 87% and 86% for possums and ship rats, respectively. Two field trials, each 200 hectares in size, targeting possums, ship rats and mice achieved an average reduction in the abundance of 94% for possums, 94% for ship rats and 80% for mice. The combination of diphacinone and cholecalciferol appears effective and has a favourable risk profile compared with second-generation anticoagulant rodenticides, such as brodifacoum. Approval of this new bait by the New Zealand Environmental Protection Agency was granted in 2018 and final registration obtained from the Ministry of Primary Industries in 2019.